A Perspective on Application of Carbon Quantum Dots in Luminescence Immunoassays - Hesari, Mahdi; Ding, Zhifeng (Frontiers in Chemistry, 2020)
Quantum dots (QDs) have been established in our daily life, for instance, in display screens and light-harvesting technologies, mainly owing to their peculiar opto-electronic features. However, toxicity of inorganic QDs, such as CdSe, CdTe, perovskites, limits their applications in biological environments for medical diagnosis and bio-imaging purposes. New generation of QDs called carbon quantum dots (CQDs) have been progressed rapidly in the past few years. CQDs have become even more popular than other carbon-based nanomaterials such as carbon nanotubes (CNTs), due to their ease of preparation, ultra-small size, biocompatibility and bright luminescence.